Education of Smart Fish Feeder Technology based on internet of things (IoT) for Catfish Farming Groups in Dham Pulo Village, Aceh Besar - Dedi Fazriansyah Putra; Ramzi Adriman; Nazaruddin Abubakar (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2022)
This community service program aimed to implement the smart fish feeder technology based in internet of things (IoT) to increase aquaculture productivity in Dham Pulo Village, Aceh Besar. The community service program consisted of three stages, namely: (1) Dissemination and training, (2) Practice and installation of smartphone/ Internet of Things-based automatic feeder to fishpond plots and (3) Evaluation in the form of focus group discussion (FGD). Implementation of this program managed to enhance the aquaculture productivity of fish farmer in Dham Pulo Village, Ingin Jaya Regency, Aceh Besar. This technology was successfully transferred to the farmers and supported less contact economy and database-based technology.